Connectors for electronic equipment. Printed board connectors with assessed quality. Detail specification for two-part modular connectors, basic grid of 2, 0 mm, with terminations on a multiple grid of 0, 5 mm Part 4-104, (15th August 1999) - British Standards Institution,
No abstract available